Development of a superporous hydroxyethyl cellulose‐based hydrogel by anionic surfactant micelle templating with fast swelling and superabsorbent properties. Issue 23 (12th February 2015) - Shi, Xiaoning; Jietang; Wang, Aiqin
ABSTRACT The self‐assembling anionic surfactant, sodium n‐dodecyl sulfonate (SDS) micelles were used as pore‐forming templating for fabricating novel superporous hydroxyethyl cellulose‐grafting‐poly(sodium acrylate)/attapulgite (HEC‐g‐PNaA/APT) hydrogels. The network characteristics, morphologies of the hydrogels and removing of SDS micelles from the final product by washing with ethanol/water (v/v, 7 : 3) procedure were determined by Fourier transform infrared spectroscopy and scanning electron microscopy, as well as by determination of swelling ratio, swelling rate, and stimuli response to salts and pHs. The results showed that the added‐SDS concentration significantly affected the morphologies and pore structure of the hydrogel, and 2 mM SDS facilitates to form a homogeneous and well‐defined pore structure in the gel network to extremely improve the swelling ratio and swelling rate. The 2 mM SDS‐added superporous HEC‐based hydrogel not only had highest equilibrium swelling ratio (Qeq, 1118, 102 g g−1 in distilled water and 0.9 wt % NaCl solution), rapid swelling rate (kis, 5.2840 g g s−1), also showed multistimulus responses to salts and pHs, which may allow its applications in several areas such as adsorption, separation and biomedical materials. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42027.